Life? Freedom? Love? — Reflections on the COVID-19 Pandemic - HE, Guanghu (Journal of Research for Christianity in China (JRCC), 2025)
This article offers a profound reflection on the relationship between life, liberty, and love in the wake of the COVID-19 pandemic. The author proposes that human interactions during this crisis should be guided by compassion and divine law, emphasizing that while humanity strives to save itself and fight against the virus, it must also seek God's mercy and assistance.